(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
This research sought to determine the management of public day secondary schools through infusion of information and communication technology. The study was carried out in Githunguri Constituency, Kiambu County, Kenya. The objective of the Study was to: determine the departments of day secondary school that have been functionally integrated with ICT, establish the strengths of integrating ICT in the running of a day secondary school. The study used descriptive research design. The study sample was 270 participants derived 22 public day secondary schools through stratified techniques. The study’s main findings were inadequate awareness by principals on the need for use of ICT integration in management, inadequate ICT resources and related infrastructure and lack of technical support for heads of departments as well as low resource mobilization by board of management influenced ICT integration in public secondary schools to a great extent. The main conclusions of the study is poor attitude towards ICT integration and inadequate resources and lack of technical support were the main hurdles towards ICT integration in school. The study recommended that principals of secondary schools work with the ministry of Education together with the Kenya Institute of Curriculum Development should come up with tailor made ICT integration programs to impart relevant skills, knowledge and attitude to school administrators. Therefore, further studies could be done on the effectiveness of use of ICT in managing secondary school affairs.